1984
DOI: 10.1007/bf00390472
|View full text |Cite
|
Sign up to set email alerts
|

A phase II study of cis-diamminedichloroplatinum II for advanced breast cancer two dose schedules

Abstract: Thirty-six (36) women with metastatic breast cancer refractory to conventional therapies were treated with cis-diamminedichloroplatinum II. Two dose schedules were used sequentially. The first 15 patients received platinum at a dose of 15 mg/m2 daily for 5 days at 28-day intervals. No response was noted in this group. Subsequently, 21 patients were treated with a dose of 100-120 mg/m2 at 28-day intervals, but with additional induced diuresis with saline, furosemide, and mannitol. Among 13 patients evaluable fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

1988
1988
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(11 citation statements)
references
References 3 publications
1
10
0
Order By: Relevance
“…Yap et al (1978) found no responders in 26 patients treated with either 100mgm-2 q 3-4 weekly or 20mgm-2 daily x 5, q 4 weekly. Ostrow et al (1980) (Forastiere et al, 1982;Martino et al, 1984;Bajorin et al, 1987). These studies are summarised in Table I which shows only ten responders out of 113 patients (overall response rate 9%).…”
Section: Cisplatinmentioning
confidence: 99%
“…Yap et al (1978) found no responders in 26 patients treated with either 100mgm-2 q 3-4 weekly or 20mgm-2 daily x 5, q 4 weekly. Ostrow et al (1980) (Forastiere et al, 1982;Martino et al, 1984;Bajorin et al, 1987). These studies are summarised in Table I which shows only ten responders out of 113 patients (overall response rate 9%).…”
Section: Cisplatinmentioning
confidence: 99%
“…Carboplatin also has activity in the first-line setting (Table 1) [7][8][9][10][11][12][13][14][15][16]. Four studies of the drug as initial chemotherapy reveal an overall RR of 31% (27 of 85 patients responded).…”
Section: Overview Of Platinum Agents In Breast Cancermentioning
confidence: 99%
“…Nevertheless, the activity of the combination is promising, and it is recommended (given the GI toxicity at higher doses) that further work be undertaken using 75 mg/m 2 of both agents. The combination of taxanes/platinum as chemotherapy for breast cancer has been studied by other investigators (Table 3) [7] No 33/66 (50%) Sledge [9] No Yap [10] Yes Ostrow [7] Yes Forestiere [7] Yes 10/113 (9%) Martino [11] Yes Bajorin [12] Yes…”
Section: Platinum/docetaxel Combinations In Breast Cancermentioning
confidence: 99%
“…It results in exposing patients to new agents when their tumor burden is high, their performance status is poor, their tumor has demonstrated resistance to other treatments, and their bone marrow reserve is limited due to previous therapy. Further, review of reports of phase II agents studied in this sequence demonstrates the frequent occurrence of 'early deaths', making it difficult to give new agents an adequate trial [1][2][3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%